Modern marvels Architectural wonders. The Empire State Building ; Eiffel Tower (New York A&E Television Networks Marketed and distributed in the U.S. by New Video Group, 2007)
This program circles the globe to profile the world's most phenomenal architectural gems: Baseball Parks, the Egyptian Pyramids, the Eiffel Tower and much more!
Originally aired on the History Channel.
"Go behind the scenes of the world's most stunning and awe-inspiring masterpieces of design and function with MODERN MARVELS.
DVD.
Keywords: Empire State Building (New York, N.Y.); Tall buildings -- United States; Tour Eiffel (Paris, France); Towers -- France; New York (N.Y.) -- History -- 1898-1951.